2014
DOI: 10.3402/fnr.v58.25707
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A status in pregnant women in Iran in 2001 and its relationship with province and gestational age

Abstract: BackgroundVitamin A deficiency is considered as one of the public health problems among pregnant women worldwide. Population representative data on vitamin A status in pregnancy have not previously been published from Iran.ObjectivesThe aim of this study was to publish data on vitamin A status in pregnant women in all the provinces of Iran in 2001, including urban and rural areas, and to describe the association of vitamin A status with maternal age, gestational age, and parity.DesignThis descriptive cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Regarding obstetric variables, there was a negative linear correlation between gestational age and serum retinol levels, which is a similar result to those found in other studies [35,36,37]. It is important to note that even if the reduction occurs with more intensity in the second and third quarter due to plasma volume expansion and increased vitamin A transfer from the mother to the fetus, special attention throughout pregnancy is necessary, particularly in the first trimester, when the major changes in the fetal development occur.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding obstetric variables, there was a negative linear correlation between gestational age and serum retinol levels, which is a similar result to those found in other studies [35,36,37]. It is important to note that even if the reduction occurs with more intensity in the second and third quarter due to plasma volume expansion and increased vitamin A transfer from the mother to the fetus, special attention throughout pregnancy is necessary, particularly in the first trimester, when the major changes in the fetal development occur.…”
Section: Discussionsupporting
confidence: 90%
“…Such a high frequency of VAD differed from the findings of other studies that also investigated its occurrence in pregnant populations. In Iran, Olang et al [35] found a VAD prevalence of 24.9% among 3270 pregnant women evaluated. In China, a study carried out by Yang et al [36] that involved 1209 pregnant women showed an inadequate prevalence in only 5.3% of the sample, while in Venezuela, a study by Ortega et al [37] was the only one with a sample of pregnant adolescents showing a 10.62% prevalence of VAD.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported here are similar to those found in China, where a frequency of VAD of 5.2% was found in a group of 1209 pregnant women evaluated in 150 urban or rural areas between 2013 and 2014 [30]. Compared to the present findings, other studies conducted in developing countries using the cut-off point of <0.70 μmol/L reported much higher prevalence rates of VAD in pregnant women: 24.6% in 3270 pregnant women in Iran [31], 20% in a sample of 80 women in Egypt [32], 18.5% in 200 women in Bangladesh [33], 15.8% in 101 women in Nigeria [34], 13.8% in 738 women in Guinea-Bissau [35], and 10.6% in 160 pregnant adolescents in Venezuela [18]. However, only the sample sizes used in the studies conducted in China, Iran, and Guinea-Bissau were large enough to yield robust data.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have shown similar results, reporting vitamin A deficiency to be more common at the end of pregnancy than at the beginning [18,30,31,35,37,52]. These findings could be explained by the increase in the maternal-fetal transfer of vitamin A due to faster fetal growth towards the end of pregnancy [53].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation